Perspectiva agroecológica sobre o Projeto de Desenvolvimento Rural Sustentável (PDRS): experiência da cooperativa Entre Serras e Águas - Furtado, Rafael Caselli (2016)
Aiming the improvement of public policies that adopt the principles of agroecology as methodologies to accomplish the rural/urban brazilian development, systematization and critical analysis of experiences becomes an indispensable tool for the development of these projects. Thus, this research chose one of the lines of action of the Projeto de Desenvolvimento Rural Sustentável (PDRS - Microbasins II), developed by the São Paulo State government with the Banco Mundial, whose the case chosen acts aiming the implementation of Agroforestry Systems (SAFs) for family farmers of the state. The case study was coordinate by the Cooperativa Entre Serras e Águas (CESA) which has more than 100 farmers of Bragança Paulista (SP) region, among these, fourteen were interested in the project pariticipation. The project began in September 2014 and was followed until May 2016. The project's critical analysis was made in the cross of understanding perspective and agroecological sociology, based on participant observation and semi-structured interviews. The systematization of perceptions of the actors involved in the project and the author critical analysis pointed to a project that still needs to evolve especially as the issues of: empowerment methodologies farmers; incorporate agroecological concepts in project design; further explore the possibilities of environmental compliance through agroforestry systems respecting the brazilian law; incorporate the social, ecological and economic dimensions in building a design adapted to the reality of farmers; dialogic action, emancipatory and continued by the Technical Assistance; and creating an appropriate market for the products generated that achieve the objective of marketing incentive. From these and other observations, suggestions were made aimed at management of CESA on the project and improvements for future PDRS projects